Lattice Proton Intercalation to Regulate WO3‐Based Solid‐Contact Wearable pH Sensor for Sweat Analysis. (8th October 2021) - Tang, Yitian; Gan, Shiyu; Zhong, Lijie; Sun, Zhonghui; Xu, Longbin; Liao, Chunxian; Lin, Kanglong; Cui, Xiaoqing; He, Dequan; Ma, Yingming; Wang, Wei; Niu, Li
Abstract: Sweat pH monitoring is a routine indicator in wearable biotechnology. The state‐of‐the‐art wearable pH sensors mostly rely on organic materials but face the risk of biological toxicity. WO3 is a typical H + ‐sensitive inorganic material with chemical stability, biocompatibility, and low cost but low sensitivity and slow response. Lattice H + intercalation is herein proposed as an efficient approach that can greatly improve the sensitivity and selectivity of WO3 ‐based pH sensors. Specifically, lattice H + intercalation can promote WO3 from the monoclinic phase to cubic phase, which enhances the ion exchange capacity between WO3 and H + . The resistance decreases more than two orders of magnitudes, which improves the interfacial charge transport. The occupancy of lattice H + leads to ion exchange only with H +, thus increasing the H + recognition. The intercalated H x WO3 exhibits much improved sensitivity, reversibility, and response time. Additionally, the H x WO3 is integrated with a solid reference electrode on a miniaturized chip for wearable sweat pH monitoring. The pH sensor exhibits good potential response even at curving over 270°. On‐body sweat pH measurments show high accuracy compared with ex situ analyses. This work emphasizes the concept of lattice proton intercalation to regulate the H + recognition of solid contacts. Abstract : An approach for electrochemical lattice proton intercalation is proposed to regulate the WO3 ‐based inorganic pH sensor. The proton intercalation enhances the conductivity and accelerates the proton transport, which overcomes the issues of low sensitivity and slow response. This proton intercalated WO3 is integrated into a wearable sensor for on‐body pH monitoring.